Optimalisasi Peran Account Officer dalam Penentuan Kelayakan Pengajuan Pembiayaan di BMT Maslahah - Saleha, Idayatus; Wisudaningsih, Endah Tri; Nasrifah, Maula (SAFE-Network, 2023)
Account Officers have an important role in increasing the efficiency of the institution. Apart from recruiting members, account officers are responsible for various tasks, such as resolving problematic financing, conducting surveys, and conducting financing analysis. accept or reject requests for financing, and become a source for sharia institutions to ensure the continuity of requests for financing. Account Officers must evaluate customers for financing and realizing funding. The purpose of this study is to identify the methods used by account officers to assess the feasibility of applying for financing at the BMT Maslahah Besuk Branch, and explain the supporting factors and inhibiting factors for Account Officers in determining the feasibility of applying for financing at the BMT Maslahah Besuk Branch and explain the solutions they make. in overcoming these inhibiting factors. To express these challenges completely and clearly, researchers used a qualitative approach with raw data collection techniques such as observation, interviews, and documentation. Additional investigations were conducted, and the conclusions reached indicated that the Account Officers modified their approach by working through five steps, including the funding stage, the data collection stage, the data analysis stage, the approval stage, and the disbursement stage. then the 5C concept is used to evaluate. Factors constraining Account Officers in determining eligibility for financing Lack of information on prospective members, inappropriate use of financing, and incomplete customer data are obstacles that must be overcome by Account Officers to assess whether or not a financing is appropriate. Reviewing the 5C principles, taking a personal approach when talking to prospective customers, conducting interviews, preparing the necessary documents, and educating prospective customers so as not to hinder the financing application process.